Metode Focus Group Discussion (FGD) dalam Peningkatan Kemampuan Berpikir Kritis Siswa Kelas VIII pada Mata Pelajaran PAI di SMP Entrepreneur Ar-Ridwan Gunung Tawang Selomerto Wonosobo - Dimas Setiawan; Mukromin Mukromin; Firdaus Firdaus (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to describe the implementation of the Focus Group Discussion (FGD) method in Islamic Religious Education (PAI) learning and its impact on improving critical thinking skills of grade VIII students at SMP Entrepreneur Ar-Ridwan Gunung Tawang Selomerto Wonosobo. The background of this study is based on the needs of 21st century learning that requires students to have critical, collaborative, and communicative thinking skills. This study uses a qualitative approach with a descriptive research type. Data collection techniques are carried out through observation, in-depth interviews, and documentation. Data analysis uses data reduction techniques, data presentation, and drawing conclusions. The results of the study indicate that the FGD method has been implemented systematically in PAI learning through the formation of small discussion groups, trigger questions, and presentation of discussion results. The teacher acts as an active facilitator who encourages student participation evenly. The positive impacts of the implementation of FGD include increased active student participation, the ability to convey arguments logically, and the growth of reflective and critical attitudes. However, the implementation of FGD also faces several obstacles such as time constraints, differences in communication skills, and the unequal distribution of student confidence in open discussions. These obstacles are overcome through classroom management strategies such as role rotation, providing discussion training, and habituating a culture of dialogue. Thus, the FGD method has proven effective in improving students' critical thinking skills and forming a collaborative and participatory learning culture.